2021
DOI: 10.1177/21676968211028005
|View full text |Cite
|
Sign up to set email alerts
|

Before and After Prohibition: Parental Communication and Modeling Associated With Emerging Adult Recreational Marijuana Attitudes and Use

Abstract: Researchers have begun examining changes in recreational marijuana use among emerging adults (EAs), however, no studies have examined the influence of parents on EA children’s marijuana use due to legalization. We sought to address this gap by using a 2019 cross-sectional online survey of 404 EA students (18–25 years; M = 20.7, SD = 1.9) about their behavioral observations and conversations with parents regarding recreational marijuana legalization in a western U.S. state. Significant increases in reports of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Additionally, in this study—and others 4–8 —cannabis and alcohol users (vs. nonusers) were more open about cannabis and alcohol, respectively 4–8 . We also found that parents in legalized nonmedical cannabis states reported greater communication about cannabis versus alcohol, which aligns with prior findings that parental communication regarding cannabis increases after cannabis legalization 15–17 . As such legislation expands, there may be key opportunities to examine parental communication with children regarding cannabis that may inform intervention strategies in other contexts.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, in this study—and others 4–8 —cannabis and alcohol users (vs. nonusers) were more open about cannabis and alcohol, respectively 4–8 . We also found that parents in legalized nonmedical cannabis states reported greater communication about cannabis versus alcohol, which aligns with prior findings that parental communication regarding cannabis increases after cannabis legalization 15–17 . As such legislation expands, there may be key opportunities to examine parental communication with children regarding cannabis that may inform intervention strategies in other contexts.…”
Section: Discussionsupporting
confidence: 84%
“…T A B L E 3 Linear regression models examining correlates of parental perceptions and communication regarding marijuana and alcohol use, N = 197. versus alcohol, which aligns with prior findings that parental communication regarding cannabis increases after cannabis legalization. [15][16][17] As such legislation expands, there may be key opportunities to examine parental communication with children regarding cannabis that may inform intervention strategies in other contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation